Correction: A power system network splitting strategy based on contingency analysis (Energies (2018) 11 (434) DOI: 10.3390/en11020434) - Saharuddin N.Z.; Abidin I.Z.; Mokhlis H.; Abdullah A.R.; Naidu K. (MDPI AG, 2023)
The authors wish to make the following corrections to this paper [1]. On page 1, the third author's name should be changed from Hazlie Mohklis to Hazlie Mokhlis. Furthermore, on page 12, in Table 1, ?1099.98 is changed to ?1117.603 in the ninth column, eighth row; and ?1061.97 changed to ?1079 in the tenth column, fourth row. The correct version of the table is thus (Table presented). The authors would like to apologize for any inconvenience caused to the readers by these changes. The manuscript will be updated, and the original version will remain available on the article webpage. 2018 by the authors. Licensee MDPI, Basel, Switzerland.